From Homeland to Hyperlink: Artificial Intelligence and the Reinvention of Diasporic Identity - Lijin, Feba; Kansal, Sushil (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
This paper interrogates how artificial intelligence reshapes diasporic identity in the twenty-first century, reconfiguring migration from embodied displacement into algorithmically mediated subjectivity. Drawing upon Chimamanda Ngozi Adichie’s Americanah, Tsitsi Dangarembga’s Nervous Conditions, and Chinelo Okparanta’s Under the Udala Trees, the study situates contemporary digital identity within postcolonial theory, critical AI studies, and data colonialism scholarship. While diasporic literature has historically foregrounded exile, hybridity, race, gender, and cultural negotiation, contemporary digital infrastructures increasingly mediate visibility and belonging through algorithmic systems. Social media platforms, predictive text technologies, and AI-driven recommendation architectures do not merely host diasporic expression; they structure it. Through engagement with Homi Bhabha, Stuart Hall, Gayatri Spivak, N. Katherine Hayles, Nick Couldry and Ulises Mejias, Safiya Umoja Noble, Shoshana Zuboff, Ruha Benjamin, and Achille Mbembe, this paper argues that artificial intelligence transforms diaspora from territorial displacement to networked positioning. Homeland becomes hyperlink; memory becomes metadata; recognition becomes algorithmic classification. Yet African women’s writing resists such reduction, insisting on embodied, gendered, and historically situated identity beyond computational abstraction. Ultimately, diasporic literature offers an ethical vocabulary for interrogating AI’s cultural authority and reasserting the irreducible human dimensions of belonging.